EXERGAMES TO REDUCE FALLS RISK IN OLDER PEOPLE IN UK ASSISTED LIVING FACILITIES: A MULTI-CENTRE, CLUSTER RCT. (11th November 2018) - Stanmore, E; Mavroeidi, A; Meekes, W; Skelton, D; Sutton, C; Benedetto, V; Todd, C; de jong, L
Abstract: Falls are the leading cause of fatal and non-fatal unintentional injuries in older people. The use of Exergames (active video-games) is a possible innovative, community-based approach to reduce falls risk. The objective of this study was to evaluate the effectiveness of a tailored physiotherapy-based Exergame programme for reducing falls risk in older residents of assisted living facilities in the UK. A multi-site, two-arm cluster randomised controlled trial with 3 month follow up of falls in eighteen assisted-living facilities in the UK was conducted. Tailored 12-week strength and balance Exergame programme, supported by physiotherapists or assistants plus standard care (physio advice and leaflet) against standard care only, in older adults dwelling in assisted living facilities. The primary outcome measure was balance as assessed by the Berg Balance scale (BBS). Secondary outcomes included fear of falling, mobility, pain, falls risk, fatigue, cognition and incidence of falls. Eighteen sites were recruited and randomised to each intervention (106 participants of which 56 Exergames; 50 control). Intention-to-treat analysis revealed that balance was significantly improved at 12 wks in the Exergame group with an adjusted mean increase in BBS of 6.18 (95% CI 2.38 to 9.97) and significant improvements in secondary outcomes of fear of falling and pain. Falls rate was significantly lower in the Exergames group (incidence rate ratio 0.40, (95%CI 0.22 to 0.74, p=0.001). Exergames, as delivered in this trial, improve balance, pain and fear of falling and may be considered as a fall prevention strategy in assistive living facilities for older people.